Relationships among electrolyzed water postharvest treatments on winegrapes and chloroanisoles occurrence in wine. (June 2019) - Giacosa, Simone; Gabrielli, Mario; Torchio, Fabrizio; Río Segade, Susana; Moar Grobas, Ana Maria; Ricauda Aimonino, Davide; Gay, Paolo; Gerbi, Vincenzo; Maury, Chantal; Rolle, Luca
Abstract: Electrolyzed water (EW) has attracted much recent attention as a high-performance, new technology for its potential use in the food industry. However, the risk of postharvest EW treatments of winegrapes destined for winemaking is the chloroanisoles formation in the final product. In the present study, we investigated the impact of postharvest grape EW and storage treatments on the occurrence of these compounds in wine, 2, 4, 6-trichloroanisole (TCA) being the main compound responsible for the cork taint off-flavor due to its extremely low perception threshold. The results revealed that the presence of TCA in the wines depended on the concentration of residual free chlorine in the must from the EW treatment. Particularly, TCA was not detected in wine when active chlorine concentrations higher than 0.005 mg/L were present in the must. Chloroanisole and chlorophenol levels in wine were strongly affected not only by EW but also by grape storage conditions (temperature, time, sunlight exposition). The results showed that the 24-hours grape storage at a controlled temperature of 20 °C in the dark, after EW treatment, resulted in the highest TCA concentrations in wines (7.3 ± 2.7 ng/L), while storage and withering in sunlight seemed to mitigate its presence in wine. This could suggest that microbiological formation of chloroanisoles may have been influenced by the storage temperature and germicidal effect of UV light. Biochemical mechanism of chloroanisoles production in grapes and wine is unknown, but the combination of residual free chlorine on the grape surface and the controlled storage conditions in the dark may have positively influenced the bio-formation of chloroanisoles and therefore their presence in wine. Graphical abstract: Unlabelled Image Highlights: The risk of postharvest electrolyzed water grape treatments is TCA presence in wine. Added free chlorine in grape must resulted in TCA presence after fermentation. Chloroanisoles and chlorophenols were also assessed in wines after grape storage. Grape storage in sunlight significantly reduced chloroanisoles contents in wine. Withering of treated grapes was not able to avoid chloroanisoles formation.